GE_GERICHTE C/20876/2016 vom 3. April 2019 - GE Cour de justice (2019)
PRESCRIPTION;ACTION EN RÉDUCTION;DÉCISION PARTIELLE;HÉRITIER RÉSERVATAIRE;DOMMAGE | CC.537.al1; CC.537.al2; CC.471.ch1; CC.522.al1; CC.533.al1; CC.474.al1; CC.475